2019
DOI: 10.3126/jpan.v8i1.26335
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression among Residents of old age homes in Eastern Nepal

Abstract: Introduction: Geriatric depression is emerging mental disorder with old age. The present study was carried out to estimate the prevalence of depression among residents of elderly homes in Eastern Nepal and to measure the severity of the symptoms of depressive disorders. Material And Method: This study involved residents of old age homes in four different districts of Eastern Nepal, the participants were heterogeneous with diverse cultural background and ethnicity. All elderly people of age 60 years and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…Women and individuals with lower educational levels tend to have higher depression scores. This finding is consistent with previous studies that have found higher rates of depression among women in nursing homes compared to men (29,30). Research has shown that women are more susceptible to depression than men (31).…”
Section: Discussionsupporting
confidence: 93%
“…Women and individuals with lower educational levels tend to have higher depression scores. This finding is consistent with previous studies that have found higher rates of depression among women in nursing homes compared to men (29,30). Research has shown that women are more susceptible to depression than men (31).…”
Section: Discussionsupporting
confidence: 93%
“…Most of the people living in the old age home in Eastern Nepal are found to have depressive symptoms among which majority have mild depressive symptoms and few have severe depressive symptoms. It depicts the miserable mental health of the elderly people in old age home (Sapkota et al, 2019). Abuse of the elderly is an important social and public health issue arising from increase in longevity because longevity increases the number of elderly as well and more at risk of elder abuse (Rai et al, 2018).…”
Section: Health Issuesmentioning
confidence: 99%